Cluster theory: an approach to innovate the industrial zone - Cam Thanh, Vu Thi (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
All nations on the way of economic development have to go through tim of industrialization in which the basic approach for any different economies is forming geographical concentration of industries called industrial zones. Vietnam has been carrying out the flourishing stage of industrial zones. However, the establishment and development of industrial zones surely remain some weaknesses, for example, the industrial zone model which has expressed the lack of systematically connectivity, the low economic effectiveness, and difficulties in protecting the surrounding environment. Whether can a new model based on Cluster Theory be a solution to the issue of reforming industrial zones in Vietnam? Code: 13032701